2018
DOI: 10.2147/cmar.s174690
|View full text |Cite
|
Sign up to set email alerts
|

Confirmed value of shear wave elastography for ultrasound characterization of breast masses using a conservative approach in Chinese women: a large-size prospective multicenter trial

Abstract: PurposeThis study aimed to investigate the value of shear wave elastography (SWE) for characterization of breast masses in a Chinese population.Patients and methodsTwo thousand two hundred seventy-three women consented to be prospectively enrolled for the characterization of breast masses with ultrasound and SWE. Breast masses were known from symptoms, palpability, and/or previous imaging screening with mammography and/or ultrasound. Correlation of SWE qualitative and quantitative features with malignancy risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…In addition, increased stiffness of surrounding tissue, such as the "stiff rim" sign, can also occur in benign lesions, 27 unlike the result in the study of. 28 The study of Xiang et al shows that hard cyclic disorders in benign lesions are associated with age and depth, internal composition, and edges of the lesions. Therefore, joint diagnosis using multiple markers is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, increased stiffness of surrounding tissue, such as the "stiff rim" sign, can also occur in benign lesions, 27 unlike the result in the study of. 28 The study of Xiang et al shows that hard cyclic disorders in benign lesions are associated with age and depth, internal composition, and edges of the lesions. Therefore, joint diagnosis using multiple markers is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…As for the qualitative SWE features, we used seven color patterns in this study ( 20 ): (1) no finding: no difference is observed at the margin of or inside the lesion with the color around the lesion (homogeneously blue); (2) vertical stripes pattern: a color is observed at the margin of or inside the lesion, which differs from the color around the lesion. The differing color extends beyond the lesion and continues vertically in cords on the cutaneous side and/or the thoracic wall; (3) spots pattern: colored areas are visible above and/or below the lesion; and (4) rim of stiffness pattern: a localized colored area appears at the margin of the lesion and creates a continuous closed circle; (5) colored lesion pattern: colored areas are heterogeneously visible inside the lesion; (6) void center pattern: There is a lack of SWE signal inside the lesion.…”
Section: Methodsmentioning
confidence: 99%
“…Conventional US (including two-dimensional gray-scale US, two-dimensional color Doppler US, and spectral Doppler US) was used to examine all solid lesions, and after comprehensive analyses, masses were classified using the Breast Imaging Reporting and Data System (BI-RADS) into the following: Class I, negative; Class II, benign; Class III, probably benign; Class IV, suspicious malignant; Class V, malignant (22). UE using a EUP L 54M scanner (50 mm, 6-13 MHz) equipped with elastography software (EUB-8500, Hitachi) was performed in the UE-mode with a pressure bar showing a digital readout [1][2][3][4][5][6][7] on the screen, which represented a comprehensive index of external and imposed external force frequencies. We selected readout 3 as the standard in our study.…”
Section: Routine Us and Uementioning
confidence: 99%
“…Ultrasound elastography (UE) is a non-invasive imaging technique, which facilitates the measurement of tumor elasticity and the early diagnosis of malignant breast tumors (1)(2)(3). Although the use of UE has been discredited in diagnosing small nodular breast tumors, previous studies have shown that UE has the advantage of distinguishing and localizing concealed and hard-to-reach small breast lesions missed by routine ultrasound (US) examinations, especially in differentiating malignant from benign tumors (2,4).…”
Section: Introductionmentioning
confidence: 99%